A Challenge In Establishing The Etiologic Of Toxic Epidermal Necrolysis In Children - Jefrizal Wirman; Gardenia Akhyar; Irdawaty Izrul; Qaira Anum (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2022)
Background: Toxic epidermal necrolysis (TEN) is a rare especially in children, acute and potentially lifethreatening. The etiology of the higher incidence of TEN in various pediatric age groups than in adults is unclear, the cause is multifactorial. TEN have known triggering events, including infections (commonly viral or mycoplasma) drugs/herbs, malignancy, vaccines, and idiopathic. Case report: We reported a case TEN of a 5 years old boy. There was a history of fever and red rash on the patient's hands 5 days ago and taken paracetamol, amoxicilin, chlorpeniramin maleat(CTM), and vitamin C, then a red patch and blisters appears 12 hours later. Physical examination: composmentis, temperature 38,80C. Dermatological state: erythemathous macules, vesicles, bulla, erosions, excoriations, crusts on the most of body. Hyperemic conjunctiva, on oral mucosa there were erythematous oedem, erosion, excoriation and reddish-blackish crust, and erosion of the genitalia. Epidermolysis was about ± 40%. Laboratory examination :leucocyte 5300/mm3 with lymphocytosis. Serum urea increases, serum bicarbonate decreases. The patient was treated dexamethasone intra venous and decreased dose with prednisone oral, patient improved and healed on day 13. Discussion: The diagnosis of TEN in patients is made based on history and physical examination. We can establish a typical diagnosis of TEN from clinical symptoms and physical examination, but to find the etiology is sometimes difficult and requires a deep history and other investigations. The etiology in this case cannot be established because of drugs or infection. To find out, it is necessary to do further tests such as serology or PCR